Catalyst and additive-free regioselective oxidative C–H thio/selenocyanation of arenes and heteroarenes with elemental sulfur/selenium and TMSCN. Issue 95 (13th November 2018) - Feng, Chengtao; Peng, Ya; Ding, Guangrong; Li, Xiangxiao; Cui, Chang; Yan, Yizhe
Abstract : Elemental sulfur/selenium and TMSCN act as a novel combined thio/selenocyanation source for direct oxidative C–H thio/selenocyanation of (hetero)arenes under catalyst-free and additive-free conditions. Abstract : A regioselective oxidative C–H thio/selenocyanation of arenes and heteroarenes with TMSCN and elemental sulfur/selenium was demonstrated under catalyst-free and additive-free conditions. Dimethyl sulfoxide (DMSO) was employed as the mild oxidant as well as the solvent. The reaction is operationally simple and scalable with a broad substrate scope.